Hubungan Fungsi Manajemen Kepala Ruangan Dengan Pelaksanaan Handover Menggunakan Komunikasi SBAR - Wulandari, Rizki Yeni; Elasari, Yunina; Nugroho, Tri Adi; Kusnita, Fani Euis (Profesi (Profesional Islam) : Media Publikasi Penelitian, 2023)
As much as 80% of the issues that result in medical errors are related to handover. One endeavor to increase patient safety at the hospital is the use of SBAR communication during handovers. The management duties of the head of the room, such as checking, directing, and evaluating the implementation of the handover, are directly tied to the effectiveness of implementing efficient communication during a handover. SBAR communication during handovers is a problem that happens in Pringsewu Hospital. The objective of this study is to determine the correlation between head management function and the implementation of handovers using SBAR communication at Pringsewu Regional Hospital. This research type is quantitative. The research design used a descriptive correlation using a cross-sectional approach. This research was conducted at the Pringsewu Regional Hospital in May 2023. The total population was 70 nurses in 5 inpatient rooms. The sampling technique uses total sampling. The data collection instrument used a questionnaire and data analysis used the Fisher's exact test. The results showed that there is a correlation between the room head management function and the implementation of handover using SBAR communication, with a p-value = 0.007. It is expected that the head of the room will improve the 5 management functions of the head of the room, especially the supervisory function so that handovers using SBAR communication can be carried out optimally.